Mobilisasi Dini Membantu Pengeluaran Lochea Pada Ibu 6 Jam Post Sectio Caesarea - Safarinda, Dwi Sindy; Umami, Riza; Subiastutik, Eni (Malang Journal of Midwifery (MAJORY), 2021)
Early mobilization is very important for post-Section Caesarea patients to help the process of uterine involution and lochea removal. Most of the post-Section Caesarea mothers are afraid to do early mobilization because they are afraid to feel post-Section Caesarea pain. The purpose of this study was to determine the relationship between early mobilization and the amount of lochia expenditure in mothers 6 hours post-Section Caesarea at Baladhika Husada Hospital. The research design used is the correlation with cross-sectional approach. The population of this study was all post-Section Caesarea mothers at Baladhika Husada Hospital. The sampling technique used is accidental sampling which was carried out from December 2019 to January 2020 with a total of 53 samples. Analysis of the data used is the chi-square test. The results of this study showed that most of the 6-hour post-SC mothers did early mobilization (54.8%) and almost half of the mothers who did early mobilization had normal lochea discharge (35.8%). The results of the analysis showed that there was a relationship between early mobilization and the amount of lochia expenditure in mothers 6 hours post-Section Caesarea (p-value 0.036). Early mobilization increases blood circulation in the uterus so that the uterus can contract properly, clamping open blood vessels and the lochia can come out smoothly. Keywords: Sectio Caesarea, Early Mobilization, Lochea Expenses.